Water-related ecosystem services in Western Siberian lowland basins—Analysing and mapping spatial and seasonal effects on regulating services based on ecohydrological modelling results. (December 2016) - Schmalz, B.; Kruse, M.; Kiesel, J.; Müller, F.; Fohrer, N.
Highlights: Assessment of water-related ecosystem services in West Siberian basins. Ecohydrological modelling results are the base for their analyses. Analyses and mapping of water flow and erosion regulation show spatial and seasonal effects. Abstract: For discussing and planning sustainable land management of river basins, stakeholders need suitable information on spatio-temporal patterns of natural processes and human actions. This study shows an approach to use ecohydrological modelling results for assessing water-related ecosystem services in three lowland river basins in Western Siberia. Based on the results of the ecohydrological model SWAT (Soil and Water Assessment Tool, Arnold et al., 1998 ), simulated output variables were used as indicators for the two regulating services water flow regulation and erosion regulation. The model results were translated into a relative ecosystem service valuation scale, which facilitates the comparison of different ecosystem services and which serves as the base for the applied mapping approach. The ecosystem service maps show different spatial and seasonal patterns. Although the daily modelling results were aggregated to seasonal maps to generate an understandable amount of information for stakeholders, differences can be depicted: during snowmelt, low regulation can be determined, especially for water flow regulation, but a very high regulation was calculated for the vegetation period during summer and for the winter period. Erosion regulation is high in two basins during all seasons. Spatio-temporal differences were modelled only for the largest basin. The SWAT model serves as a suitable quantification method for the assessment of the selected water-related regulating services.